INTEGRATION OF DIGITAL TECHNOLOGIES INTO THE DEVELOPMENT OF GLOBAL MARKETING COMMUNICATIONS OF INDUSTRIAL ENTERPRISES - ZAKRYZHEVSKA, Iryna; NEDIELIN, Yevhenii; OSTAPCHUK, Serhii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
In the context of economic globalization and digital business transformation, the system of marketing communications in industrial enterprises is undergoing profound changes driven by market interconnectedness, complex business processes, and increasing demands for strategic information management. The formation of effective global marketing communications has become a key factor of competitiveness, ensuring not only the dissemination of information but also the creation of trust, corporate reputation, and sustainable partnerships. The relevance of this study lies in the need to develop a systematic approach to the advancement of marketing communications in industrial enterprises, integrating digital technologies, data analytics, intercultural competence, and corporate social responsibility.The main problem arises from the fragmentation of communication channels, uneven levels of digital maturity, and insufficient integration of analytical tools into decision-making processes. As a result, enterprises face information gaps, inconsistency of messages, and a decline in global communication efficiency. Addressing these challenges requires the formation of an integrated model of global marketing communications that maintains brand consistency while allowing flexibility in adapting to the cultural characteristics of target markets.The study identifies five key vectors for the development of global marketing communications in industrial enterprises: integration and systematization of channels (IMC approach), digitalization and analytical decision support, cross-cultural adaptation, content orientation, and social responsibility. Based on these directions, a scientific and practical model of communication architecture has been developed, combining strategic, analytical, and operational management levels. This model enables the creation of a unified digital communication space integrating clients, suppliers, and partners, thereby enhancing transparency, information exchange efficiency, and the overall competitive position of enterprises in the global market.The findings confirm that an effective system of global marketing communications in the industrial sector relies on the harmonious integration of technological, analytical, and cultural components. Such integration fosters strategic flexibility, strengthens interaction management, and forms a coherent brand communication space. Ultimately, it enables industrial enterprises to adapt successfully to the challenges of the global digital economy and ensure sustainable development in the international marketplace.
Keywords: global marketing communications; industrial enterprises; digitalization; integrated marketing communications (IMC); cross-cultural adaptation; content marketing; data analytics; social responsibility; strategic flexibility